Pelibatan Mahasiswa dalam Pemetaan Visitor dan Potensi Wisata di Kompleks Percandian Plaosan - ., Khaerunnisa; Sakti, Gerland Biworo; Putri, Veronica Clarysta; Angelica, Michelle Natasha; Gumawang, Yos Risang Abdi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2025)
Field-based learning activities are an integral part of developing architectural students’ competencies, especially in the field of cultural tourism and heritage conservation. This paper describes students’ experiences in mapping visitors and tourism potential at the Plaosan temple complex. The focus is on the learning process involving field observation, primary data collection through surveys and interviews, and the analysis of spatial and activity potentials. Through participatory and collaborative approaches, students applied theories of tourism and cultural heritage conservation in real contexts while enhancing their skills in data collection and spatial mapping. This documentation of student activities is expected to serve as a reference for community-based and conservation-oriented field learning methods applicable in architectural education.